Relationship between knowledge and attitude about human papillomavirus infection and vaccination in female nursing students - Silaban, Delima Rosalina; Blegur, Jeane Kornalia; Marbun, Ruth Nataly; Cathryne, Joice; Lebdawicaksaputri, Kinanthi (Gaceta Médica de Caracas, 2024)
Introduction: Human papillomavirus (HPV) infection is the primary cause of cervical cancer, which is the second-leading cause of women’s death in Indonesia, and that is why a national HPV vaccination program is required to address this issue. A preliminary survey of 20 female nursing students revealed that 70% were unaware of the HPV virus, 80% were unaware of cervical cancer, and 80% were unaware that HPV could lead to cervical cancer. This study aimed to determine the relationship between knowledge and attitude about human papillomavirus infection and vaccination in female nursing students. Methods: This descriptive-quantitative study used a cross-sectional design and univariate and bivariate analysis.